Biomimetic materials based on hydroxyapatite patterns for studying extracellular cell communication; Materials & Design; Vol. 238 - Zyrianova P. I. Polina; Eltantawy M. M. Mervat; Silin D. V. Danil; Korolev I. S. Ilya; Nikolaev K. G. Konstantin; Kozodaev D. A. Dmitry; Slautina A, S. Alla; Surmenev R. A. Roman Anatolievich; Kholkin A. L. Andrei Leonidovich; Ulasevich S. A. Sviatlana; Skorb E. V. Ekaterina (2024, 2024)
Title screen